Cover Picture: steel research int. 5/2017. Issue 5 (May 2017) - Karimi‐Sibaki, Ebrahim; Kharicha, Abdellah; Wu, Menghuai; Ludwig, Andreas; Bohacek, Jan
Abstract : Electrochemical reactions always occur at the electrode‐slag and slag‐metal melt interfaces during the electroslag remelting (ESR) process. The cover shows a schematic representation of this process. A numerical model is developed to investigate those reactions together with the ion transport phenomenon. The cover figure is supplied by Christian Doppler Laboratory for Advanced Process Simulation of Solidifi cation and Melting. Further details can be found in the article by Menghuai Wu and co‐workers, article1700011 .